KOMPETENSI KHUSUS AKUNTAN FORENSIK (SURVEI PADA AKUNTAN FORENSIK KAP BIG FOUR DI INDONESIA) - Christine Linardo; yulius Jogi Christiawan (Business Accounting Review, 2016)
This study aimed to analyze the nine competencies of forensic accountants.These skills including deductive analysis ability, creative thinking skill, unstructuredproblem solving competence, investigative flexibility, analytical proficiency, oralcommunication ability, written communication ability, specific legal knowledge andgood composure to (1) determine whether or not special competency requiredfor forensic accountants and (2) identify a new set of variables (factors) to replace thenine competency variables at the Big Four public accounting firms in Indonesia.This study was conducted by census to all the population. Data were obtainedby distributing 140 questionnaires to all auditors who were working as associates inthe forensic division at the Big Four public accounting firms in Indonesia. Data were while Exploratory Factor Analysis used to answer the second objective. The dataanalysis were performed with SPSS version 20.The results of this study by using Spearman Rank Correlation Analysisshowed that special competencies were required for the work of forensic accountants.By using Exploratory Factor Analysis, the results identified that three factors wouldbe reduced from nine competency factors of forensic accountants. The first factorincluding deductive analysis ability, unstructured problem solving competence,investigative flexibility, and analytical proficiency. The second factor includingcreative thinking skill, specific legal knowledge and good composure while the thirdfactor including oral communication ability and written communication ability.